(untitled) (Journal of Economic Research & Business Administration, 2019)
This article is devoted to the study of the possibilities for the application of foreign experience in the development of project and innovation management at the enterprises of the defense industry of the Republic of Kazakhstan (DI RK). For this purpose, a study was conducted on the experience of implementing project activities in various countries and identifying features. Given the fact that in the development of innovation and project management, some countries have advanced far ahead, it seems useful to study their experience in implementing effective management systems in the country’s defense industry enterprises. Military power and competitiveness are taken as a criterion to identify the countries on which to focus for the study and application of their experience. The current state and development trends of the defense industrial complex of other countries, as well as the experience of international companies in the implementation of innovation and project activities, have been studied. The study used data from international organizations, country statistics, global indices and ratings. Among the scientific literature studied the works of foreign and domestic authors on related topics. The study showed that the implementation of project activities in different countries occurs at different speeds. As the experience of other countries has shown, the increase in the amount of funding, in itself, does not ensure the country’s military competitiveness. The development of the military sector depends on many factors, in addition to the amount of funding, among which innovativeness of projects, people’s competence, development of management systems and others are especially important. The practical significance of this work lies in the fact that the findings and proposed recommendations can be useful in the recently initiated processes of introducing innovative and project management in the Ministry of Defense and Aerospace Industry, in general, and in defense enterprises, in particular.